Dietary intakes of alkaline metals, alkaline earths and phosphorus in Ukrainians - Zamostyan, Pavlo V.; Tsigankov, Nikolay Y.; Ko, Susumu; Los, Ivan P.; Shiraishi, Kunio; Koruzun, Vitaly N. (Biomedical Research on Trace Elements, 2009)
Dietary intakes of alkaline metals (Na, K, Rb, and Cs), alkaline earths (Ca, Mg, Sr, and Ba) and phosphorus (P) in Ukrainian subjects were estimated in relation to the health effects on residents after the Chernobyl accident. Two hundred and sixty-eight diet samples were collected from 25 oblasts (regions) using a duplicate portion method. The elements were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) or inductively coupled plasma mass spectrometry (ICP-MS). For Ukrainians, median daily intakes per person were as follows: Na 4.08 g; K 2.89 g; Rb 2.19 mg; Cs 3.78 μg; Ca 0.696 g; Mg 0.254 g; Sr 1.88 mg; Ba 0.507 mg; and P 0.991 g. The intakes of Na, K, Ca, and Mg were almost the same as worldwide reported values, while those of Sr and Ba were higher and Cs and P were lower than those values.